HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN KEDISIPLINAN BELAJAR DENGAN HASIL BELAJAR SISWA SEKOLAH DASAR - Anjelika Widyasari; Hamdani Hamdani; Dyoty Auliya Vilda Ghasya (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
Abstract This study aims to describe the relationship between emotional intelligence and learning discipline with learning outcomes in thematic learning. The method used is ex post facto research with a type of correlation research. The population in this study was all VA class students of State Elementary School 39 Pontianak Kota with sampling using a simple random sampling technique of 16 students. The data collection techniques used in the study were in the form of questionnaires and tests about class V learning outcomes theme 9 subtheme 2. Data analysis techniques use the product moment formula. The results of the calculation of the product moment correlation between emotional intelligence and learning outcomes were 0.591, between learning discipline and learning outcomes of 0.670, between emotional intelligence and learning discipline of 0.461. The results of the calculation of the double correlation of product moment between emotional intelligence and learning discipline with learning outcomes obtained = 0.581> = 0.497. So it can be concluded that Ha accepted there is a relationship between emotional intelligence and learning discipline with learning outcomes in thematic learning of grade V students of State Elementary School 39 Pontianak Kota with a moderate level of correlation. Keywords: Emotional Intelligence, Learning Discipline, Learning Outcomes